Synergism of 2-(3,4-dichlorophenoxy)triethylamine and top removal enhances maize lodging resistance and yield via coordinated photosynthetic optimization and phenylpropanoid pathway activation - Xie, Tenglong; Wang, Meiyu; Yang, Xiaoge; Ma, Yihe; Zhang, Baoyu; Zhang, Qian; Mei, Linlin; Yang, Deguang (Frontiers in Plant Science, 2025)
IntroductionPlant growth promoters like 2-(3,4-dichlorophenoxy) triethylamine (DCPTA) increases maize yield but heightens lodging risk. We investigated whether integrating canopy top removal (TR) with DCPTA application resolves this trade-off.MethodsOver 2023–2024 seasons, maize plants were treated with DCPTA, TR, or both. Assessments included: the basal 8th leaf photosynthesis; strength, phenylpropanoid enzyme activity, and structural components deposition in the basal 3rd internode; plus grain yield and lodging incidence.ResultsTR counteracted DCPTA-induced suppression of basal leaf photosynthesis and carbon assimilation. Crucially, the combination synergistically enhanced assimilate flux to basal stalks. This influx, potentiated by DCPTA, significantly upregulated phenylpropanoid enzymes versus TR alone, driving enhanced deposition of structural components. Specifically, during the grain-filling stage, the combination significantly enhanced chlorophyll content, gas exchange parameters (Pn and Gs), and PSII photochemical efficiency (Fv/Fm, ΦPSII, and ETR) in the basal 8th leaf, while reducing NPQ, thereby optimizing overall photosynthetic performance. Consequently, stem strength markedly increased. Over 2023–2024 growing seasons, the integrated strategy consistently increased grain yield: the TR+DCPTA treatment increased grain yield by 5.64%/4.56% vs. DCPTA alone, 3.45%/3.69% vs. TR alone, and 9.34%/8.19% vs. the control, respectively. Meanwhile, lodging incidence dropped significantly by 81.25% (2023) and 70.18% (2024) compared with sole DCPTA application.DiscussionThe synergy arises because TR alleviates DCPTA’s negative effects on basal leaf function, while DCPTA potentiates the phenylpropanoid pathway’s response to the assimilate surge triggered by TR. This reciprocal interaction enables simultaneous optimization of photosynthetic efficiency in source leaves and robust activation of stem strengthening mechanisms, achieving higher yield and lodging resistance.